2018
DOI: 10.3390/ijms19092575
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-2 Controls the Motility of RAB5 Endosomes and Their Association with the Spindle in Mitosis

Abstract: RAB5 is a small GTPase that belongs to the wide family of Rab proteins and localizes on early endosomes. In its active GTP-bound form, RAB5 recruits downstream effectors that, in turn, are responsible for distinct aspects of early endosome function, including their movement along microtubules. We previously reported that, at the onset of mitosis, RAB5positive vesicles cluster around the spindle poles and, during metaphase, move along spindle microtubules. RNAi-mediated depletion of the three RAB5 isoforms dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The LC–MS analysis revealed that KIF3A associated with multiple progress regulators related to the cell cycle, cytoskeleton, transport, and membrane organelles. Similarly, a previous study found that depletion of KIF3A and KIF3B impairs the long-distance transport of RAB5 endosomes in interphase cells, resulting in delayed nuclear membrane rupture and prolonged prophase [ 41 ]. In addition, another study found that ablation of KIF3A can reduce the cell proliferative capacity in a microtubule-dependent manner [ 43 ].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The LC–MS analysis revealed that KIF3A associated with multiple progress regulators related to the cell cycle, cytoskeleton, transport, and membrane organelles. Similarly, a previous study found that depletion of KIF3A and KIF3B impairs the long-distance transport of RAB5 endosomes in interphase cells, resulting in delayed nuclear membrane rupture and prolonged prophase [ 41 ]. In addition, another study found that ablation of KIF3A can reduce the cell proliferative capacity in a microtubule-dependent manner [ 43 ].…”
Section: Discussionmentioning
confidence: 74%
“…As a kinesin, KIF3A has been reported to play an important role in cilia formation, osteogenic development, and mitosis of various cell types [ 41 , 42 ]. Previous studies have demonstrated that KIF3A is distributed mainly on spindle microtubules and centrosomes during mitosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This Special Issue also contains four original research articles reporting the novel function of specific Rab GTPases and their regulation. Pupo et al [ 22 ] investigated the role of the Rab family small GTPase Rab5, which is localized in the early endosomes, in the regulation of mitosis. Kinesin-2 was proposed to participate in the movement of Rab5-containing endosomes and their localization at the spindle, and the endosomal transport at the onset of mitosis was suggested to be required to control the timing of nuclear envelope breakdown.…”
mentioning
confidence: 99%